Bidirectional shifts in Pm20d1 expression impact thermogenesis and metabolism - Simoes, Marcela R.; Gallo-Ferraz, Ana L.; Bombassaro, Bruna; Valdivieso-Rivera, Fernando; Nogueira, Guilherme A. S.; Monfort-Pires, Milena; da Cruz; Marcos Vinicius; Zanesco, Ariane M.; Fernanda-Oliveira, Nayra; Silveira, Leonardo Reis; Castilho, Roger F.; et al. (Springer Science and Business Media LLC, 2026)
Background
Peptidase M20 domain containing 1 (PM20D1) is a secreted N-fatty acyl amino synthase and hydrolase that controls tissue and blood levels of N-fatty acyl amino acids. In brown adipocytes, N-fatty acyl amino acids bind to mitochondria and act as uncouplers of mitochondria, independent of UCP1. Interventions aimed at increasing or inhibiting PM20D1 expression considerably impact energy balance and metabolism; however, little is known about naturally occurring variants of the PM20D1/Pm20d1 gene and their impact on phenotype.
Methods
In vivo, gene expression of Pm20d1 in BALB/c, C57BL/6, and Ucp1 KO in brown adipose tissue and other metabolic tissues was measured. In vitro, transcriptional activity of Pm20d1 and brown adipocytes’ oxygen consumption in primary culture were assessed. Human PM20D1 circulating levels were quantified. In silico analysis of the Pm20d1 gene sequencing and human polymorphisms associated with PM20D1 was performed.
Results
Here, we identified a gain-of-function variant in the Pm20d1 promoter region present in BALB/c mice and absent in C57BL/6 mice. The presence of this variant is accompanied by increased expression of Pm20d1 in brown and white adipose tissues, muscle, liver, and hypothalamus; moreover, it leads to increased cold tolerance and UCP1-independent brown adipose tissue mitochondrial respiration. Inhibition of Pm20d1 in brown adipose tissue results in defective cold tolerance in BALB/c, whereas the brown adipose tissue overexpression of Pm20d1 results in increased cold tolerance in C57BL/6 mice. In humans, variants of the PM20D1 gene are associated with changes in body mass index, whereas at least one variant in the promoter region is associated with increased body mass index and metabolic syndrome.
Conclusion
Thus, PM20D1 plays a bidirectional role in regulating thermogenesis and body mass, and, at least in part, variants in the promoter region can partially explain the differences in PM20D1 expression and its impact on the metabolic phenotype.